Effect of Concentration on the Formation of Rose Bengal Triplet State on Microcrystalline Cellulose: A Combined Laser-Induced Optoacoustic Spectroscopy, Diffuse Reflectance Flash Photolysis, and Luminescence Study - Litman, Yair Ezequiel (2014)
Laser-induced optoacoustic spectroscopy (LIOAS), diffuse reflectance laser flash photolysis (DRLFP), and laser-induced luminescence (LIL) have been applied in conjunction to the determination of triplet state quantum yields of Rose Bengal (RB) supported on microcrystalline cellulose, a strongly light-scattering solid. Among the three used methods, the only one capable of providing absolute triplet quantum yields is LIOAS, but DRLFP and LIL aid in demonstrating that the LIOAS signal arises in fact from the triplet state and confirm the trend found with RB concentration. The coherence found for the three techniques demonstrates the usefulness of the approach. Observed triplet quantum yields are nearly constant within a limited concentration range, after which they decay strongly due to the generation of inactive dye aggregates or energy trapping centers. When quantum yields are divided by the fraction of absorbed light exciting the dye, the quotient falls off steadily with concentration, following the same trend as the observed fluorescence quantum yield. The conditions that maximize triplet formation are determined as a compromise between the rising light absorption and the decrease of quantum yield with RB concentration.